Diversity of Lactobacillus Species of Stilton Cheese Relates to Site of Isolation - Mugampoza, Diriisa; Gkatzionis, Konstantinos; Swift, Benjamin M. C.; Rees, Catherine E. D.; Dodd, Christine E. R. (Frontiers in Microbiology, 2020)
Τhis study has characterized the dominant non-starter Lactobacillus species isolated from different sites in a Stilton cheese to establish its diversity, stress-tolerance, anti-microbial activity and potential contribution to quality of cheese. Fifty-nine Lactobacillus isolates were cultured from the outer crust, blue veins and white core of the cheese and were speciated phenotypically and by 16S rDNA sequence analysis. L. plantarum was the dominant species detected with only two isolates identified as L. brevis. Strains were typed by pulse-field gel electrophoresis (PFGE) using the enzyme NotI to examine their genomic diversity. Cluster analysis of PFGE patterns produced five major clusters which associated isolates with their sites of isolation within the cheese. One L. plantarum isolate from each cheese site was selected and evaluated for salt, acid, relative humidity and heat tolerance to determine whether stress conditions within the isolation site selected their phenotype. D72°C values were 6, 13 and 17 s for strains from the crust, veins and core, respectively, suggesting strains on the crust may not have been able to survive pasteurization and therefore had been added post-pasteurization. All strains recovered from heat injury within 24-48 h at 4oC. pH values of 3, 3.5 and 4 suppressed growth but strains showed a varying ability to grow at pH 4.5 and 5; isolates from the core (which has the lowest pH) were the most acid-tolerant. All strains grew at 3.5 and 5% salt but were suppressed at 10%; those from the crust (which has a lower water activity) were the most halo-tolerant, growing at 8% salt whereas strains from the core were sensitive to this salt concentration. All 57 L. plantarum isolates were examined for antimicrobial activity and variable activity against L. pentosus and other genera was demonstrated; plantaricin EF genes were present in 65% of strains. It was concluded that there are varied phenotypes and genotypes of Lactobacillus in a Stilton cheese according to site of isolation. Occurrence of different L. plantarum genotypes could contribute to variation in the cheese quality from batch to batch and provides criteria for selecting isolates as potential adjunct cultures.